THE IMPORTANCE OF LEGISLATION IN PROMOTING AGROECOLOGY (Interdisciplinary Studies Journal, 2024)
This article looks at the importance of legislation in promoting Agroecology, highlighting the potential of law to encourage ethical and more sustainable production practices. It looks at how legislation can shape agroecology in practice, through regulations in a number of areas, including the use of pesticides and fertilisers, the protection of farmers' rights and the promotion of policies that encourage sustainable agricultural practices. The article reviews global examples of legislation that promote agroecologically-based crops, with a special focus on the Common Agricultural Policy in Europe, government policies in Brazil and Cuba. Challenges and opportunities for promoting agroecology as a science through legislation are discussed here, addressing aspects such as the influence of corporate and political interests, as well as growing awareness of the negative impacts of climate change and demands for more sustainable food systems.
Keywords: Agroecology; Regulations; Agricultural Policy; Sustainable Agriculture